Prevalence of malnutrition in under five age group of the tribals in Wayanad district of Kerala, South India: a community based cross-sectional study - S. R., Arun Krishna; Srijayanth, Parameswari (International Journal Of Community Medicine And Public Health, 2022)
Background: Malnutrition is one of the major causes for childhood mortality among under-five children in India. The tribal community accounts for 8.6% of India's population. In India, nutritional as well as socio-economic inequalities are most intensely experienced by the tribal population when compared with the rest of the population. The objective of the study is to estimate the prevalence of malnourishment among tribal children (0-59 months) in the Wayanad district of Kerala. Methods: A community-based cross-sectional survey was conducted among 319 tribal children (0-59 months) of Noolpuzha panchayat, Wayanad district using a semi-structured, pretested questionnaire to collect the socio-demographic profile (age, gender, education, occupation, type of tribe, type of house, type of family) from mother/caretaker and anthropometric measurements (height, weight, and mid-arm circumference) was recorded and compared with WHO growth standards. Quantitative variables were summarized using the Mean (SD). Children below -2SD are considered malnourished in terms of being underweight, stunted, and wasted. Results: The mean age of the children were 29 months±16 SD of which 168 (52.7%) were male, and 151 (47.3%) were females. The prevalence of underweight, stunting, and wasting was 175 (54.8%), 165 (51.7%) and 99 (31%) respectively of which 111 (34.7%) were severely underweight, 88 (27.6%) were severely stunted and 57 (17.8%) were severely wasted. Conclusions: Malnourishment in the form of stunting, wasting, and underweight is very high among under-five tribal children of Noolpuzha panchayat resulting in the need for a multidisciplinary approach to identifying the reasons for malnourishment existing among these marginalized communities.